Legal Frameworks for Addressing the Human Rights Violations Linked to Illegal Mining: A Call for Government Accountability and Sustainable Solutions. - Nodangala, Norless Zibele (Eastasouth Institute, 2025)
The paper aimed to examine the critical intersection between human rights and environmental law, focusing on the urgent implications of governmental inaction regarding illegal miners threatened and killed by starvation underground at the Stilfontein mine in Klerksdorp, North-West. The Constitution of the Republic of South Africa (“The Constitution”) protects human and environmental rights. This paper argues that inefficiencies of government regulation increase such destructive practices, resulting in significant ecological harm and systemic human rights abuses. This paper critically examines governmental negligence and the legal obligations of states regarding human rights and environmental issues. Additionally, the paper advocates for a multidisciplinary approach that integrates human rights with environmental legislation. The study found that though there are legal frameworks around mining, there is no monitoring and accountability of these mining companies. The paper advocates for solid legal frameworks that bridge human rights and environmental protections, emphasising the necessity for governmental accountability in addressing the illicit mining crisis and its implications on vulnerable communities. The author recommends robust legal frameworks to address illegal mining and the economic vulnerabilities driving individuals to illicit activities.